3x-43+3=

Simple and best practice solution for 3x-43+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-43+3= equation:


Simplifying
3x + -43 + 3 = 0

Reorder the terms:
-43 + 3 + 3x = 0

Combine like terms: -43 + 3 = -40
-40 + 3x = 0

Solving
-40 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '40' to each side of the equation.
-40 + 40 + 3x = 0 + 40

Combine like terms: -40 + 40 = 0
0 + 3x = 0 + 40
3x = 0 + 40

Combine like terms: 0 + 40 = 40
3x = 40

Divide each side by '3'.
x = 13.33333333

Simplifying
x = 13.33333333

See similar equations:

| y-7+10-4x+6x+2y= | | (8k-1)(4k-3)=0 | | 126=2x+2(2x-6) | | 5x+7=75 | | (4c+2g)(4c-2g)=0 | | 2x^2-8x+8=0 | | 8x+6-3x-8+2y-6y= | | 7(k-6)+8=-13 | | 0.2(500-2.3x)=3.8(3x-3000) | | 2k^2-18= | | -252=-7(x+19) | | 4x-1=2x-31 | | -44x+28y+4= | | (4w-2)(5w+4)=0 | | 18m+27=2m-3 | | -4-6x=-64 | | y-5y= | | m(m+4)(m-7)=0 | | 3(3x-1)=4(4x-1) | | 4s+8=12 | | x+11=314.86 | | -14(9+19p)=3066 | | 12(x-7)=60 | | X^2+x=2 | | 4p^2-5pq= | | 252=x+.8x | | 3(y+7)=4(y-2) | | 3m-8m=10 | | 4=p+14 | | 3x^2(4x+5)(x-6)=0 | | -6(2p+2)-24=4(3p+3) | | 4p^4-5pq= |

Equations solver categories